The double-edged sword effect of conscientiousness on the work engagement of medical staff in Chinese public hospitals - Sun, Hui; Hua, Xuelu; Wu, Shibing; Sun, Ling (Frontiers in Public Health, 2025)
BackgroundIn China, medical staff in public hospitals are the primary providers of healthcare services. Their work engagement directly affects patients’ perceptions of the level and quality of their medical services. Conscientiousness has a significant impact on the work engagement of medical staff, but the mechanism between the two is not yet clear.ObjectiveThis study examined the double-edged sword effect of conscientiousness on medical staff work engagement, with a particular focus on exploring the mediating effects of thriving at work (TAW) and workload, as well as the moderating effect of perceived insider status (PIS).MethodsThe study sample was drawn from four public hospitals in the Jiangsu Province, Shanghai City, and Zhejiang Province. Data were statistically analyzed using SPSS, and mediation and moderations effects tested were conducted through the Bootstrap method.ResultsThe results demonstrate the following: (1) conscientiousness has a positive effect on the work engagement of medical staff; (2) conscientiousness has a positive effect on work engagement through thriving at work (TAW), and a negative effect on work engagement through workloads; (3) perceived insider status (PIS) moderates the relationship between conscientiousness and TAW, and the relationship between conscientiousness and workloads; and (4) PIS moderates the indirect effect of conscientiousness on work engagement through TAW, whereas the mediated relationship is strengthened when medical staff members exhibit a higher PIS. Simultaneously, PIS moderates the indirect effect of conscientiousness on work engagement through workload, and the mediating relationship is weakened for medical staff members who have a higher PIS.ConclusionThis study provides a balanced and dialectical understanding of the impact of conscientiousness, providing significant reference for enhancing the work engagement of medical staff in public hospitals.